2017
DOI: 10.1002/pen.24539
|View full text |Cite
|
Sign up to set email alerts
|

Composites made from a soybean oil biopolyurethane and cellulose nanocrystals

Abstract: Cellulose nanocrystals (CNC) obtained by acidic hydrolysis from microcrystalline cellulose were dispersed in a biopolyurethane matrix to prepare composite films. The polyurethane was prepared from a hydroxylated soybean oil (SO‐OH) and a polymeric diphenyldiisocyanate (pMDI), using a organotin compound as the catalyst. The composite films contained different concentrations of nanocelullose, without any macroscopic aggregates in all cases. Thermal, tensile and dynamic mechanical properties of the films were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…As CNF loading increased, the nanocomposite film approached the percolation threshold (agglomeration), lowered the area of physical interaction, and resulted in a stress deficiency transfer. This area of heterogeneous and agglomeration has become a stress concentrator and a failure point for nanomaterials [ 39 ]. Gao et al [ 37 ] also reported a similar observation.…”
Section: Resultsmentioning
confidence: 99%
“…As CNF loading increased, the nanocomposite film approached the percolation threshold (agglomeration), lowered the area of physical interaction, and resulted in a stress deficiency transfer. This area of heterogeneous and agglomeration has become a stress concentrator and a failure point for nanomaterials [ 39 ]. Gao et al [ 37 ] also reported a similar observation.…”
Section: Resultsmentioning
confidence: 99%
“…In effect, formulations which have a highly cross‐linked nature will also have a higher weight percent of isocyanate precursors. However, the main drawback of this strategy is that most of the research that has been performed in the development of bio‐based polyurethane precursors is associated to the polyol component 19–21 . Hence, a material with a higher renewable content will be difficult to attain because the main component of the RPUF is the isocyanate.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main drawback of this strategy is that most of the research that has been performed in the development of bio-based polyurethane precursors is associated to the polyol component. [19][20][21] Hence, a material with a higher renewable content will be difficult to attain because the main component of the RPUF is the isocyanate. To surmount this issue, another strategy can be based on the use of nanotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnological utilization of cellulose broadens its utility in the form of fibers [ 1,3,24,25 ] as well as crystals [ 26–28 ] for several sophisticated applications. Recently, CNFs and silica‐based composite aerogels [ 29–31 ] have gained much attention from researchers due to several unique features of CNFs, such as their ultra‐lightweight, high elastic modulus, and low thermal expansion.…”
Section: Introductionmentioning
confidence: 99%